The effect of indigenous non-Saccharomyces yeasts on the volatile profile of Maraština wine: Monoculture versus sequential fermentation - Ana Boban; Urska Vrhovsek; Silvia Carlin; Vesna Milanović; Jasenka Gajdoš Kljusurić; Zvonimir Jurun; Irena Budić-Leto (Applied Food Research)
Non-Saccharomyces yeasts are presented as a new promising tool in winemaking to enhance aroma complexity in fermentation with Saccharomyces yeasts. Indigenous yeasts are recognized for their better adaptation to environmental conditions and for highlighting the unique terroir impact on wine aroma characteristics. To study the individual impact of ten indigenous non-Saccharomyces yeasts on the primary metabolites and volatile compounds of wine from autochthonous Croatian Maraština variety, Hyphopichia pseudoburtonii, Metschnikowia chrysoperlae, Metschnikowia sinensis/shanxiensis, Metschnikowia pulcherrima, Lachancea thermotolerans, Hanseniaspora uvarum, Hanseniaspora guilliermondii, Hanseniaspora pseudoguilliermondii, Pichia kluyveri, and Starmerella apicola were inoculated in sterile grape juice in monoculture fermentations. Additionally, seven of them were also studied in sequential fermentation of sterile grape juice with commercial Saccharomyces cerevisiae. A targeted approach was used for the identification of volatile compounds via headspace solid-phase microextraction coupled with gas chromatography and a mass spectrometer. P. kluyveri and H. uvarum produced higher total concentrations of terpenes in sequential versus monoculture fermentation. Sequential fermentation of M. chrysoperlae, L. thermotolerans, and P. kluyveri with S. cerevisiae resulted in higher production of C13-norisoprenoids. The esters concentration was higher in monocultures for L. thermotolerans, H. uvarum, and H. guilliermondii, whereas other isolates showed higher concentrations in sequential fermentations. The results highlighted different indigenous yeast metabolisms and provided promising insights into potential new non-Saccharomyces starter cultures as a first step in their selection, with several species characterized in terms of their potential effect on the aroma profile.